Cover Feature: SnS2 Nanosheets/H‐TiO2 Nanotube Arrays as a Type II Heterojunctioned Photoanode for Photoelectrochemical Water Splitting (ChemSusChem 5/2019). Issue 5 (4th March 2019) - Lin, Jianfei; Liu, Yong; Liu, Yongping; Huang, Chen; Liu, Wenhui; Mi, Xihong; Fan, Dayong; Fan, Fengtao; Lu, Huidan; Chen, Xiaobo
Abstract : The Cover Feature shows a SnS2 nanosheet/hydrogenated‐TiO2 ‐Nanotube Array Photoanode for visible light‐driven water splitting. Through hydrogen treatment, defects are created in TiO2 nanotubes, which converts a type I junction to type II in the presence of SnS2 . More information can be found in the Communication by Lin, Liu et al. onpage 961 in Issue 5, 2019 (DOI:10.1002/cssc.201802691 ).